2020
DOI: 10.1002/ardp.201900320
|View full text |Cite
|
Sign up to set email alerts
|

Systematic response of staurosporine scaffold‐based inhibitors to drug‐resistant cancer kinase mutations

Abstract: Human protein kinases have been established as promising druggable targets in cancer therapy. However, a large number of acquired drug-resistant kinase mutations are observed after first-and second-line kinase inhibitor treatments, largely limiting the application of small-molecule inhibitors in the targeted cancer therapy.Previously, the pan-kinase inhibitor staurosporine and its derivatives have been reported to selectively inhibit gatekeeper mutants over wild-type kinases, suggesting that the staurosporine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Clinical behavior based on the molecular and biological mechanisms of anti-cancer drug-sensitive cancer and drug-resistant cancer is distinct [12,13]. Many researchers have focused on making a difference by analyzing the span of mutations between anti-cancer drug-sensitive cancer and drug-resistant cancer [14][15][16][17][18][19][20]. However, the mechanism of the molecular distinctions to fully determine the anti-cancer drug-resistantmediated poor prognosis in patients with PTC is undetermined.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical behavior based on the molecular and biological mechanisms of anti-cancer drug-sensitive cancer and drug-resistant cancer is distinct [12,13]. Many researchers have focused on making a difference by analyzing the span of mutations between anti-cancer drug-sensitive cancer and drug-resistant cancer [14][15][16][17][18][19][20]. However, the mechanism of the molecular distinctions to fully determine the anti-cancer drug-resistantmediated poor prognosis in patients with PTC is undetermined.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have focused on the effects of staurosporine. However, as a broadly selective and effective protein kinase inhibitor, it has been hypothesized to play an essential role in treating tumor drug resistance [ 33 ]. Its exact role needs to be further defined.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that clinical behavior based on molecular and biological mechanisms is different between anti-cancer drug-sensitive cancer and resistant cancer [ 11 , 12 , 13 ]. Therefore, several studies have shown that the range of mutations affects anti-cancer drug-sensitive and -resistant cancers [ 14 , 15 , 16 , 17 , 18 , 19 ]. Many previous studies have demonstrated molecular diversities to clarify the poor prognosis of PTC in anti-cancer drug-resistant patients; however, to the best of our knowledge, no study has yet provided a clear description of the underlying mechanism.…”
Section: Introductionmentioning
confidence: 99%